2017
DOI: 10.1159/000477998
|View full text |Cite
|
Sign up to set email alerts
|

Chest Compressions during Sustained Inflations Improve Recovery When Compared to a 3:1 Compression:Ventilation Ratio during Cardiopulmonary Resuscitation in a Neonatal Porcine Model of Asphyxia

Abstract: Background: Recently, sustained inflations (SI) during chest compression (CC) (CC+SI) have been suggested as an alternative to the current approach during neonatal resuscitation. No previous study compared CC+SI using CC rates of 90/min to the current 3:1 compression:ventilation ratio (C:V). Objective: To determine whether CC+SI versus a 3:1 C:V reduces the time to the return of spontaneous circulation (ROSC) and improves hemodynamic recovery in newborn piglets with asphyxia-induced bradycardia. Intervention a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 33 publications
(41 reference statements)
1
45
0
Order By: Relevance
“…We have previously demonstrated that using CC+SI with a PIP of 30 cmH 2 O significantly improves ROSC and survival in asphyxiated newborn piglets, compared to using the coordinated 3:1 compression-to-ventilation ratio (C:V) [18,19,21]. However, the optimal PIP for delivering SI during CC remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that using CC+SI with a PIP of 30 cmH 2 O significantly improves ROSC and survival in asphyxiated newborn piglets, compared to using the coordinated 3:1 compression-to-ventilation ratio (C:V) [18,19,21]. However, the optimal PIP for delivering SI during CC remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive studies during the last decade, the most effective method of delivering CC remains controversial. We have previously demonstrated that providing a sustained inflation (SI) during CC (CC+SI) significantly improves return of spontaneous circulation (ROSC) and survival in newborn piglets [18][19][20][21]. Our primary aim was to determine whether different PIP during CC+SI would affect time to ROSC and survival in newborn piglets with asphyxia-induced asystole.…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that during neonatal CPR, different C:V ratios do not improve outcomes and might not be the optimal CC approach in newborn infants. In comparison with the recommended 3: 1 C:V, combining CC with sustained inflation has been shown to be more effective in improving ROSC in piglets [15, 22-24], but not in lambs [25]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the duration of CPR or C:V ratios did not change the levels of lung inflammation. Similarly, different CC techniques (e.g., 3: 1 C:V vs. CC during sustained inflation) did not increase levels of lung inflammation [15]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation